Analysis Of Ta'zir Fund Management For Default Customers In Improving Customer Discipline At PT. BPRS Puduarta Insani - Siti Febriana; Abdul Hadi Ismail (Penerbit Merdeka Kreasi, 2023)
The purpose of this study is to find out how PT. BPRS Puduarta Insani in managing Ta'zir funds to Default customers in improving customer discipline. The method used in this study is a qualitative approach. PT. BPRS Puduarta Insani offers several products both in raising funds, distributing funds and other services. PT. BPRS Puduarta Insani often experiences arrears problems caused by negligence and unwanted circumstances occur. So PT. BPRS Puduarta Insani applies Ta'zir to customers who make delays whose purpose is to anticipate that there will be no delays for customers in carrying out their obligations. In Fatwa DSN-MUI No. 17/DSN-MUI/IX/2000 states that Ta'zir applies to customers who can afford but deliberately delay payments. Based on the results of the company's decree PT. BPRS Puduarta Insani large Ta'zir applied at the bank is 0.00069 per day, and 2% for 1 month, the size of the percentage of Ta'zir depends on the length of time the customer is in arrears in payment installments. There is a way done by PT. BPRS Puduarta Insani to default customers who deliberately delay payments, namely by giving special attention or approaches such as conducting regular monitoring and providing advice, the aim of which is that customers are on time in paying financing installments, if customers continue to delay payments, PT. BPRS Puduarta Insani will issue warning letters I, II, III to customers and if there is no change, confiscation of collateral will be carried out.